Digital and Industry 4.0 technologies in olive farming and industry: recent applications and future outlook - Parra-López, Carlos; Abdallah, Saker Ben; Hassoun, Abdo; Jagtap, Sandeep; Garcia-Garcia, Guillermo; Hassen, Tarek Ben; Trollman, Hana; Trollman, Frank; Carmona-Torres, Carmen (Elsevier, 2025)
Vital to the economy, culture and landscape of many regions around the world, the olive sector faces significant challenges, including rising production costs, labour shortages, climate change impacts, water scarcity, quality control issues and market demands for transparency and authenticity. Digital and other Industry 4.0 technologies offer transformative potential to address these pressures. This article provides a comprehensive review of recent applications and future prospects of technologies such as the Internet of Things, Artificial Intelligence, Machine Learning, Robotics and Automation, Big Data Analytics, Advanced Sensing, Remote Sensing, Nanotechnology and Blockchain across the olive value chain, from cultivation to supply chain management. Using a literature review methodology to identify key application areas, it synthesises evidence on how these innovations increase resource efficiency, optimise farm management, automate labour-intensive tasks, improve pest and disease control, ensure product quality and authenticity, facilitate traceability and add value through by-product valorisation. Key benefits include improved yields, reduced environmental impact, enhanced quality control, fraud deterrence and increased consumer confidence. Future prospects include deeper integration of technologies, more sophisticated AI-driven decision support, advanced robotics, widespread adoption of rapid sensing techniques, development of circular economy models and nanotechnology applications, while recognising the need for safety assessments. Overcoming barriers related to cost, digital literacy, data interoperability and equitable access, especially for smallholder farmers, is critical. This review highlights the strategic importance of embracing digital transformation to strengthen the resilience, sustainability and competitiveness of the global olive industry.
Keywords: 46 Information and Computing Sciences; 4609 Information Systems; Machine Learning and Artificial Intelligence; 9 Industry, Innovation and Infrastructure; 12 Responsible Consumption and Production; Olea europaea; Olive; Digital transformation; Agri-food technology; Precision agriculture; Smart farming